Experiencing accessibility of historical heritage places with individuals living with visible and invisible disabilities - Ruiz-Rodrigo, Alicia; Morales, Ernesto; Lakoud, Maryem; Riendeau, Jonathan; Lemay, Miranda; Savaria, Ariane; Mathieu, Samuel; Feillou, Isabelle; Routhier, François (Frontiers in Rehabilitation Sciences, 2024)
Introduction. Around 16% of world's population lives with visible and invisible disabilities. People with disabilities' participation may be limited because of the environmental obstacles. Moreover, historic heritage places were built before the development of accessibility standards and the rights of people living with disabilities and the majority were not designed to be accessible. Access to historic heritage places is important for carrying out the activities in place but also to create and reinforce identity. The aim of this study was to explore the experiences of people with visible and invisible disabilities when visiting heritage sites considering accessibility issues. Methods. This study is a qualitative interpretive description. Participants were adults with visible (e.g., motor disability) or invisible (e.g., autism) disabilities. For data collection, go along interviews in two different locations in the Historic District of Old Quebec in Quebec City were conducted. Thematic analysis was done.Results. Twenty-one participants completed two go along interviews: one in the Séminaire de Québec (Seminary of Quebec City) and the other in Petit-Champlain and Place Royale areas of Quebec City. Three themes emerged: 1) Obstacles and impact on participation; 2) Disabling accessibility; and 3) Heritage meaning. Discussion. The barriers identified by participants are diverse and differ according to the person and the type of disability. However, social and leisure activities were particularly limited, despite the strategies developed by some participants. Participants in the study demonstrated an interest in accessing to heritage places, therefore it seems essential to consider the needs of people with disabilities when developing accessibility solutions, and to seek a balance between preserving heritage and promoting inclusive and equitable access for all.